PENGARUH KEPATUHAN WAJIB PAJAK ORANG PRIBADI DENGAN SANKSI PAJAK SEBAGAI VARIABEL MODERASI - Rima Pricillia Angelina; Sawidji Widoatmodjo (Jurnal Kontemporer Akuntansi, 2024)
The purpose of this study was to analyze the effect of service quality, tax socialization, and financial conditions ontaxpayer compliance with the application of tax sanctions as a moderating variable at the West Bekasi Primary TaxService Office. This research method uses quantitative methods by distributing questionnaires to the West BekasiPrimary Tax Service Office. The population in this study is the West Bekasi Primary Tax Service Office. So that thesample used in this study amounted to 60 samples. The research results prove that the quality of tax services has anot effect on taxpayer compliance. Tax socialization has a not effect on taxpayer compliance. Taxpayer financialcondition has a positive and significant effect on taxpayer compliance Tax sanctions cannot moderate therelationship between the quality of tax services and mandatory compliance. tax sanctions moderate the relationshipof tax socialization to taxpayer compliance. Tax sanctions moderate the relationship between the taxpayer'sfinancial condition and taxpayer compliance